Complete Edentulism of Dental Patients in Northeastern Turkey: Prevalence and Radiographic Findings on Panoramic Radiographs - Sadik, Elif; Kara, Cankat; Gökmenoğlu, Ceren (Journal of Dentistry Indonesia, 2020)
The prevalence of complete edentulism varies from country to country and from one region to another. Previous studies have reported the high prevalence of significant radiographic findings in edentulous patients. Objectives: This study aimed to determine the prevalence of complete edentulism retrospectively and to evaluate the frequency and location of significant radiographic findings on panoramic radiographs in edentulous jaws of dental patients in northeastern Turkey. Methods: The digital panoramic images of all ≥35 year-old patients admitted to our faculty from January 2014 to August 2015 were evaluated. The prevalence of complete edentulism was determined among 8314 panoramic images retrospectively. Radiographic findings identified as impacted teeth, retained roots, radiopaque, and radiolucent areas detected in panoramic radiographs of completely edentulous patients (CEP) were recorded. The obtained data were analyzed with descriptive statistics and cross-tabs. Chi-square test was employed to evaluate the statistical significance of the results at 0.05 levels. Results: A total of 8314 panoramic images were examined, and 508 (6.11%) CEP were defined. The prevalence of edentulism was higher (24.85%) among the patients older than 64 years old. A total of 206 radiographic findings were detected on panoramic images of CEP. The prevalence values of retained roots, impacted teeth, radiopacities, and radiolucencies were 18.9%, 7.09%, 2.76%, and 1.57%, respectively. Conclusions: Given the high frequency of significant radiographic findings, the radiographic examination of CEP should be performed with consideration of the cumulative effects of radiation.